Quality management of english learning during the pandemic of Islamic Elementary School Tahfizh Al-Qur’an El Ma’mur Bogor - Nusantari, Widhya; Rosyadi, A. Rahmat (Tawazun: Jurnal Pendidikan Islam, 2023)
During the Covid-19 pandemic, there has been a change in learning patterns, from face-to-face learning patterns to distance learning. This change in learning patterns poses a challenge for teachers to be able to manage virtual classes into effective classes. This study aims to describe the implementation of quality management of English language learning from the perspective of Islamic education during the pandemic at Tahfizh AL-Quran El Ma’mur Islamic elementary school in Bogor. The method used in this research is field research with a qualitative approach, which can be interpreted as a series or process of capturing information, from natural conditions in the life of an object, related to solving a problem, both from a theoretical and practical point of view. This research begins with collecting information in a natural situation. The implementation of English language learning from the perspective of Islamic education will have an impact on progress and quality if it is carried out in a planned manner such as using syllabus, lesson plans and online teaching media. This also makes the learning process efficient even though learning is carried out in the midst of a pandemic. Abstrak Pada masa pandemi Covid-19, telah terjadi perubahan pola pembelajaran, dari pola pembelajaran tatap muka ke pembelajaran jarak jauh. Perubahan pola pembelajaran tersebut, menimbulkan tantangan bagi para guru agar mampu mengelola kelas virtual menjadi kelas yang efektif. Penelitian ini bertujuan untuk mendeskripsikan implementasi manajemen mutu pembelajaran bahasa Inggris perspektif pendidikan Islam selama masa pandemi di sekolah dasar Islam Tahfizh Alquran El Ma’mur Bogor. Metode yang digunakan dalam penelitian ini adalah studi lapangan (field research) dengan pendekatan kualitatif yakni dapat diartikan sebagai rangkaian atau proses menjaring informasi, dari kondisi sewajarnya dalam kehidupan suatu obyek, dihubungkan dengan pemecahan suatu masalah, baik dari sudut pandang teoritis maupun praktis. Penelitian ini dimulai dengan mengumpulkan informasi-informasi dalam situasi sewajarnya. Pelaksanaan pembelajaran Bahasa Inggris perspektif pendidikan Islam akan berdampak maju dan berkualitas jika dilaksanaan dengan terencana seperti menggunakan Silabus, RPP dan media ajar daring. Hal ini juga membuat proses pembelajaran efisien meski pembelajaran dilaksanakan di tengah pandemi.